2015
DOI: 10.1021/jacs.5b05313
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of n-Alkanes by Solid-Phase Molecular Pincer-Iridium Catalysts. High Yields of α-Olefin Product

Abstract: We report the transfer-dehydrogenation of gas-phase alkanes catalyzed by solid-phase, molecular, pincer-ligated iridium catalysts, using ethylene or propene as hydrogen acceptor. Iridium complexes of sterically unhindered pincer ligands such as (iPr4)PCP, in the solid phase, are found to give extremely high rates and turnover numbers for n-alkane dehydrogenation, and yields of terminal dehydrogenation product (α-olefin) that are much higher than those previously reported for solution-phase experiments. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
119
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 91 publications
3
119
1
Order By: Relevance
“…The Ir-pincer catalysts, such as Ir(PCP iPr )(C 2 H 4 ) [PCP iPr = κ 3 -C 6 H 3 -2,6-(CH 2 P i Pr 2 ) 2 ], recently reported by Goldman and co-workers, promote the transfer dehydrogenation, and subsequent double-bond isomerization, of butane, pentane and octane using acceptors such as tert -butylethene, ethene or propene. 45 , 46 These operate at temperatures of 200 °C or above in sealed-tube conditions in which all the alkane is expected to be in the gas phase, and can actually outperform homogeneous systems in terms of activity. Experimental evidence points towards a presumed molecular species as the active catalyst, although the precise details have not been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…The Ir-pincer catalysts, such as Ir(PCP iPr )(C 2 H 4 ) [PCP iPr = κ 3 -C 6 H 3 -2,6-(CH 2 P i Pr 2 ) 2 ], recently reported by Goldman and co-workers, promote the transfer dehydrogenation, and subsequent double-bond isomerization, of butane, pentane and octane using acceptors such as tert -butylethene, ethene or propene. 45 , 46 These operate at temperatures of 200 °C or above in sealed-tube conditions in which all the alkane is expected to be in the gas phase, and can actually outperform homogeneous systems in terms of activity. Experimental evidence points towards a presumed molecular species as the active catalyst, although the precise details have not been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Thef unctionalization by C À Ha ctivation (via intermediate s-complexes) of simple,light, but low-value hydrocarbons, such as butane and pentane,isimportant for their conversion into valuable products that can then enter the chemical feedstock chain. [15] Although s-complexes of light alkanes have been characterized in situ by low temperature NMR and TRIR techniques, [16] published examples that have been structurally characterized are highly disordered (heptane-Fe-porphyrin), [9] or characterized as being mainly electrostatic in nature (K + /alkane). [11] Powder neutron diffraction studies at 4-8 Ks how the binding of ethane or propane with an Fe center in am etal-organic framework.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Although s-complexes of light alkanes have been characterized in situ by low temperature NMR and TRIR techniques, [16] published examples that have been structurally characterized are highly disordered (heptaneFe-porphyrin), [9] or characterized as being mainly electrostatic in nature (K + /alkane). [11] Powder neutron diffraction studies at 4-8 Ks how the binding of ethane or propane with an Fe center in am etal-organic framework.…”
mentioning
confidence: 99%
“…Beside the grafting approach, alternative heterogenization methods of Ir pincer complexes have been reported that exploit covalent attachment to a resin, tethering to silica, adsorption onto γ ‐alumina, or even the use of pure solid‐phase catalyst. [10]…”
Section: Introductionmentioning
confidence: 99%